Evaluation of the Use of Personal Protective Equipment in the Welding Process at the Arjasa District Welding Workshop - Muammar Kadhafi (Collaborate, 2023)
Personal Protective Equipment (PPE) is a safety tool workers use to protect themselves from potential hazards or work accidents in the workplace environment. Based on the Regulation of the Minister of Manpower and Transmigration No. 8 of 2010, employers or administrators are required to provide PPE by Indonesian National Standards or applicable standards. This research was conducted in a welding workshop in Arjasa Subdistrict using a survey method. The results showed that the availability of PPE was 76%, welding helmets were 68%, welding goggles were 73%, welding masks were 68%, gloves were 78%, safety shoes were 73%, welding clothes were 65%, and the conditions of the welding workshop were the appropriate standard of 74%. From these results, the use of PPE in the Arjasa District welding workshop is quite good.